The effect of lavender aromatherapy on the sleep quality of elderly patients: A quasi-experimental study - Aprilia, Rike; Akbar, M Agung; Rizki, Fakhri (Indonesian Journal of Health Services, 2024)
Background: Sleep disturbances are common among elderly individuals and negatively affect physical health, psychological well-being, and overall quality of life. Non-pharmacological approaches such as lavender aromatherapy have increasingly been used to improve sleep quality across different populations. Objective: This study aimed to examine the effect of lavender aromatherapy on sleep quality among elderly patients. Methods: This study applied a quasi-experimental design with a pretest–posttest control group approach. A total of 60 elderly participants were recruited and randomly allocated into two groups consisting of 30 participants in the intervention group and 30 participants in the control group. The intervention group received lavender aromatherapy through a diffuser for 30 minutes each night before bedtime for 14 consecutive days, while the control group received routine care without aromatherapy exposure. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) before and after the intervention period. Statistical analysis was performed using paired t-tests to evaluate changes in sleep quality within each group and independent t-tests to compare differences between the intervention and control groups. The level of statistical significance was set at p < 0.05. Results: The mean PSQI score in the intervention group decreased from 11.3 ± 2.1 at baseline to 6.2 ± 1.8 after the intervention, whereas the control group showed no significant change. Statistical analysis demonstrated significant differences between pretest and posttest scores in the intervention group and significant differences between groups after the intervention. Conclusion: Lavender aromatherapy significantly improves sleep quality among elderly patients and may serve as an effective complementary intervention in geriatric nursing care.